Defining the spatial patterns of historical land use associated with the indigenous societies of eastern North America. (25th July 2014) - Munoz, Samuel E.; Mladenoff, David J.; Schroeder, Sissel; Williams, John W.; Bush, Mark
Abstract Aim To review and synthesize multiple lines of evidence that describe the spatial patterns of land use associated with prehistoric and early historical Native American societies in eastern North America in order to better characterize the type, spatial extent and temporal persistence of past land use. Location Temperate forests of eastern North America, and the Eastern Woodlands cultural region. Methods Ethnohistorical accounts, archaeological data, historical land surveys and palaeoecological records describing indigenous forms of silviculture and agriculture were evaluated across scales ranging from local (100 km) to regional (102 km) to produce a synthetic description of land‐use characteristics. Results Indigenous land‐use practices created patches of distinct ecological conditions within a heterogeneous mosaic of ecosystem types. At all scales, patch location was dynamic, and patches underwent recurrent periods of expansion, contraction and abandonment. Land‐use patches varied in their extent and persistence, and are broadly categorized as silvicultural (management of undomesticated woodland taxa) or agricultural (cultivation of domesticated taxa). Silvicultural patches persisted for centuries and extended kilometres to tens of kilometres around settlements and travel corridors. The dynamics of agricultural patches varied among groups, with persistence ranging from decades to centuries and extent ranging from less than a kilometre to tens of kilometres around settlements. Beyond patch boundaries, human impacts on ecosystems become indistinguishable from other drivers of environmental heterogeneity. These characteristics of patches are evident across scales and multiple lines of evidence. Main conclusions Our findings challenge the view that prehistoric human impacts on vegetation were widespread and ubiquitous, and build on previous work showing these impacts to be more localized and heterogeneous by providing quantitative descriptions of land‐use patch characteristics. Collaborative efforts that combine multiple data sources are needed to refine these descriptions and generate more precise measures of land‐use pattern to further investigate the history of human impacts on the Earth system.